Class II malocclusion with accentuated occlusal plane inclination corrected with miniplate: a case report - Marcel Marchiori Farret; Milton M. Benitez Farret
ABSTRACT Introduction: A canted occlusal plane presents an unesthetic element of the smile. The correction of this asymmetry has been typically considered difficult by orthodontists, as it requires complex mechanics and may sometimes even require orthognathic surgery. Objective: This paper outlines the case of a 29-year-old woman with Class II malocclusion, pronounced midline deviation and accentuated occlusal plane inclination caused by mandibular deciduous molar ankylosis. Methods: The patient was treated with a miniplate used to provide anchorage in order to intrude maxillary teeth and extrude mandibular teeth on one side, thus eliminating asymmetry. Class II was corrected on the left side by means of distalization, anchored in the miniplate as well. On the right side, maxillary first premolar was extracted and molar relationship was kept in Class II, while canines were moved to Class I relationship. The patient received implant-prosthetic rehabilitation for maxillary left lateral incisor and mandibular left second premolar. Results: At the end of treatment, Class II was corrected, midlines were matched and the canted occlusal plane was totally corrected, thereby improving smile function and esthetics.